An investigation of the treatment efficacy of permeable pavements for water quality performance in South Africa - Schieritz, René (Department of Environmental and Geographical Science, 2017)
Stormwater pollution has been recognised as a leading cause of ecological degradation of urban streams. Sustainable Drainage Systems (SuDS) attempt to address stormwater impacts by flow attenuation and pollutant treatment, simultaneously providing amenities such as water for use in irrigation or other suitable uses. Permeable pavements are a form of SuDS that provide on-source treatment and storage of stormwater while retaining the functionality of hardened surfaces. They have been studied extensively in the international literature but no studies in a South African context have been published. This study investigated the water quality performance of a recently constructed permeable pavement at the University of Cape Town. Effluent quality was assessed against the South African Water Quality Guidelines and an ecosystem assessment tool. The results showed that, while the pavement had been constructed with unwashed aggregate and therefore exported suspended solids, effluent still met the standards required for irrigation and some industrial uses. However, the effluent did not meet desirable nutrient standards for discharge into the aquatic ecosystem. The performance of the pavement was similar to values reported in the international literature, suggesting that the quality ranges can be extrapolated to other permeable pavements. The newly constructed pavement displayed noteworthy inter-event progression, as well as identifiable intra-event variation of pollutant concentrations. Further research into effluent toxicity, long-term impacts of unwashed aggregate and catchment-wide impacts of permeable pavements are recommended.